Cannabis entrepreneurship: A guide to core concepts, resources, and research strategies. Issue 1 (2nd January 2023) - Ritchie-Baum, Morgan; Levandowski, Andrea; Toane, Carey; Cramer, Steven
Abstract: The cannabis industry is a complex set of industries involving consumer, medical, and industrial products and services. NAICS classification and government data usually provide limited value to North American researchers supporting cannabis entrepreneurship, particularly since the United States federal government (unlike that of Canada) does not yet recognize the legalization of cannabis. Social equity continues to be one motivation for cannabis entrepreneurship, given this historic targeting of U.S. and Canadian people of color for cannabis-related criminal offenses. Nonprofits and provincial, state, and local governments are now providing support for people of color working in this industry. In addition to government data, proprietary databases, trade associations, consulting firms, and boutique data and analytics firms provide data and analysis to research the cannabis industry and support its entrepreneurs.